Financial signaling by innovative nascent entrepreneurs - David B. Audretsch; Werner Bönte; Prashanth Mahagaonkar (University of Wuppertal, Schumpeter School of Business and Economics, 2009)
External finance is central for nascent entrepreneurs, people in the process of starting new ventures. We argue that nascent entrepreneurs use patents and prototypes in order to signal their ability to appropriate the returns from their innovation as well as the project's feasibility. Our analysis of 900 nascent entrepreneurs finds that patents and prototypes increase the likelihood of obtaining equity finance. Thus, if signals are credible, innovation positively impacts external financing. Interestingly, entrepreneurs in planning versus early start-up stage portray different signaling effects, indicating that the relation between finance and innovation depends on the stage of a start-up lifecycle.
urn:nbn:de:hbz:468-20090062
Keywords: L26; M13; G14; G24; G32; O34; 330; Innovation; Entrepreneurship; Finance; Information Asymmetries; Unternehmensgründung; Risikokapital; Eigenkapital; Patent; Produkt; Signalling; Finanzierung; USA